Determinants of intentions to purchase travel online: A holistic approach - Amaro, Suzanne (2015)
Online travel shopping has attracted researchers due to its significant growth and there is a growing body of literature in this field. However, research on what drives consumers to purchase travel online has typically been fragmented. In fact, existing studies have largely concentrated on examining consumers’ online travel purchases either grounded on Davis’s Technology Acceptance Model, on the Theory of Reasoned Action and its extension, the Theory of Planned Behaviour or on Roger’s model of perceived innovation attributes, the Innovation Diffusion Theory. A thorough literature review has revealed that there is a lack of studies that integrate all theories to better understand online travel shopping. Therefore, based on relevant literature in tourism and consumer behaviour, this study proposes and tests an integrated model to explore which factors affect intentions to purchase travel online. Furthermore, it proposes a new construct, termed social media involvement, defined as a person’s level of interest or emotional attachment with social media, and examines its relationship with intentions to purchase travel online. To test the 18 hypotheses, a quantitative approach was followed by first collecting data through an online survey. With a sample of 1,732 Worldwide Internet users, Partial Least Squares analysis was than conducted to assess the validity and reliability of the data and empirically test the hypothesized relationships between the constructs. The results indicate that intentions to purchase travel online is mostly determined by attitude towards online shopping, which is influenced by perceived relative advantages of online travel shopping and trust in online travel shopping. In addition, the findings indicate that the second most important predictor of intentions to purchase travel online is compatibility, an attribute from the Innovation Diffusion Theory. Furthermore, even though online shopping is nowadays a common practice, perceived risk continues to negatively affect intentions to purchase travel online. The most surprising finding of this study was that Internet users more involved with social media for travel purposes did not have higher intentions to purchase travel online. The theoretical contributions of this study and the practical implications are discussed and future research directions are detailed.